ALLOCATION OF COLLECTIVE PRODUCT COSTS USING THE MARKET PRICE METHOD - Firda Zulfa Fahriani (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The research to calculate joint cost allocation aims to calculate the cost of goods and determine inventory for external reporting purposes. Design/methodology/approach – A method of the market price using described in the data. Data sources used in a study is using the secondary data that is a source of research conducted by researchers indirectly through the intermediary ( obtained and recorded by other parties )the one that was already there. Findings – Based on the findings and discussion in the preceding chapter, it is feasible to conclude that joint products are the number of products created and sold at the same time that have the same amount or selling value but are not considered the main product or by-product. A fee will almost certainly be charged for processing a product. Research limitations/implications – The application of the market price approach in allocating the cost of joint products results in the cost of production of each product is lower than the market value of each product that has been estimated, according to the calculations. Originality/value – Because the selling price or market value can reflect the number of expenses incurred, the market price approach is frequently referred to as the most acceptable and appropriate method. It makes further on a theory in a particular science. Keywords: Joint Cost, Market Price, Joint Product Paper type: Literature Study